Industry funding of university research and scientific productivity - Hanna Hottenrott; Susanne Thorwarth (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
University research provides valuable inputs to industrial innovation. It is therefore not surprising that private sector firms increasingly seek direct access through funding public R&D. This development, however, spurred concerns about possible negative long-run effects on scientific performance. While previous research mainly focused on a potential crowding-out of scientific publications through commercialization activities such as patenting or the formation of spin-off companies, we study the effects of direct funding from industry on professors' publication and patenting efforts. Our analysis on a sample of 678 professors at 46 higher education institutions in Germany shows that a higher share of industry funding of a professor's research budget results in a lower publication outcome both in terms of quantity and quality in subsequent years. For patents, we find that industry funding increases their quality measured by patent citations.
Older version: http://hdl.handle.net/10419/43867
Keywords: O31; O32; O33; 330; Scientific Productivity; Research Funding; Academic Patents; Technology Transfer; Hochschulforschung; Forschungsfinanzierung; Forschungskooperation; Patent; Publikationsanalyse; Schätzung; Deutschland